"LET'S BE INDEPENDENT TOGETHER": ENABLING STUDENT AUTONOMY WITH TEAM BASED LEARNING ACTIVITIES IN A FLIPPED CLASS. Issue 2 (3rd April 2021) - Hass, Ashley; Laverie, Debra A.; Cours Anderson, Kelley
ABSTRACT: Marketing faculty face a complex challenge in preparing students for the modern marketplace. Today, marketing roles require creativity, problem-solving, curiosity, and the ability to learn continuously. Marketing educators can help students develop autonomy to solve problems and cultivate new ideas as lifelong learners. Innovative pedagogical tools, such as team-based learning activities and flipped class environments, offer promise for students to develop autonomy. Specifically, this quantitative study investigates how autonomy is built through interactions with peers and the instructor using team-based learning activities in a flipped class setting. We find support that a flipped class with team-based active learning cultivates autonomy, which is positively related to student perceptions of the student learning outcomes and traditional pedagogy. We offer guidance for implementing this innovation.